Childhood Executive Function Continues to Predict Outcomes in Young Adult Females with and Without Childhood-Diagnosed ADHD - Miller, Meghan (2012)
We prospectively followed an ethnically and socioeconomically diverse sample of preadolescent girls with ADHD (n=140) and matched comparison girls (n=88) over a period of 10 years, from middle childhood through late adolescence/young adulthood. Our aim was to examine the ability of childhood measures of executive function (EF) to predict functional outcomes at follow-up. Measures of EF comprised the childhood predictors, with academic, socioemotional, occupational, and global functioning serving as young adult criterion measures. Results indicated that childhood EF – particularly measures of global EF and working memory – predicted academic and occupational functioning across our entire sample (independent of diagnostic group status), but diagnostic status (ADHD versus comparison) moderated the association between (a) working memory and reading achievement and (b) a global EF measure and suspensions/expulsions. That is, in the ADHD group, low working memory predicted poor reading scores and impaired global EF predicted higher suspensions/expulsions, but this was not the case in the comparison group. Overall, these results extend previous findings of associations between EF and adolescent outcomes in girls with and without ADHD into young adulthood. Findings continue to suggest the importance of assessing and developing interventions that target EF impairments early in life in order to prevent long-term difficulties across a range of important functional domains.